2008
DOI: 10.1007/s10498-008-9029-0
|View full text |Cite
|
Sign up to set email alerts
|

Major Ion Chemistry in a Freshwater Coastal Lagoon from Southern Brazil (Mangueira Lagoon): Influence of Groundwater Inputs

Abstract: This paper characterizes major ion distributions and investigates whether groundwater exerts a major control on the chemical functioning of Mangueira Lagoon, a large (90 km long), shallow (*4-5 m deep), and fresh coastal lagoon in southern Brazil. Water volumes equivalent to *80% of the total annual input are used in the summer for irrigating nearby rice plantations, the most important regional economic activity. While Na + and Cl -are the major ions in local groundwater, Na + and HCO 3 -are the most enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 24 publications
0
10
0
4
Order By: Relevance
“…These patterns support our initial hypothesis that canals are acting as conduits for CO 2 to the atmosphere by facilitating the inputs of carbon-rich groundwater to surface waters. Artificial canals and drains may cut through aquitards and function as a window to the aquifer (de Weys et al, 2011;Santos et al, 2008). As a result, canals and drains may be considered groundwater discharge hotspots.…”
Section: Drivers Of Pco 2 Distributionmentioning
confidence: 99%
“…These patterns support our initial hypothesis that canals are acting as conduits for CO 2 to the atmosphere by facilitating the inputs of carbon-rich groundwater to surface waters. Artificial canals and drains may cut through aquitards and function as a window to the aquifer (de Weys et al, 2011;Santos et al, 2008). As a result, canals and drains may be considered groundwater discharge hotspots.…”
Section: Drivers Of Pco 2 Distributionmentioning
confidence: 99%
“…In a coastal lagoon from southern Brazil, for example, groundwater accounted for only about 2% of total water inputs. However, as the concentrations of dissolved species in groundwater are very high, groundwater-derived fluxes of major ions were equivalent to about 50% of their total annual inputs (Santos et al, 2008b).…”
Section: Relevance To the Water Budgetmentioning
confidence: 99%
“…It has been shown that lagoon systems are heterogeneous and dynamic systems. The quality of the water and subsequent seawater quality or adjacent groundwater quality strongly depends on the water flow and origin of water and nutrients (Gattacceca et al, 2009;Niencheski et al, 2007;Santos et al, 2008a, b). Land use can impact the interaction of lagoon with surrounding groundwater resulting in lagoon infiltration processes under pine tree plantations compared to negligible interactions under natural dune vegetation (Schmidt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%